2022
DOI: 10.1038/s41598-022-17106-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of pine sawdust biochar supporting phosphate-solubilizing bacteria as an alternative bioinoculant in Allium cepa L., culture

Abstract: We produced and characterised biochar made from Caribbean pine sawdust as raw material. The biochar (BC500) was used as biocompatible support to co-inoculate phosphate solubilizing bacteria (PSB) (BC500/PSB) on Allium cepa L., plants at a greenhouse scale for four months. The three biomaterials study included proximate analysis, elemental analysis, aromaticity analysis, scanning electron microscopy, Fourier transform infrared spectroscopy (FTIR), adsorption studies at different pH and PSB stability as a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Meanwhile, the rich nutrients of biochar itself can also guarantee the reproduction of microorganisms (Cooper et al, 2020). Blanco-Vargas et al (2022) also confirmed that biochar is an excellent biological inoculant to support the growth of phosphate-solubilizing bacteria. Therefore, the use of biochar to improve the efficiency of soil microbial remediation is a more effective strategy.…”
Section: The Solubilizing Effect Of Psm Makes It Difficult To Remedia...mentioning
confidence: 79%
“…Meanwhile, the rich nutrients of biochar itself can also guarantee the reproduction of microorganisms (Cooper et al, 2020). Blanco-Vargas et al (2022) also confirmed that biochar is an excellent biological inoculant to support the growth of phosphate-solubilizing bacteria. Therefore, the use of biochar to improve the efficiency of soil microbial remediation is a more effective strategy.…”
Section: The Solubilizing Effect Of Psm Makes It Difficult To Remedia...mentioning
confidence: 79%
“…Another production condition considered to improve the biochar quality was a pre-treatment, introducing it into an anaerobic hood to reduce the O 2 before the DRMM co-pyrolysis process at 300 and 500 °C. These systems involve a chemical catalyst that generates hydrogen; this gas combines with O 2 to form water and progressively reduces its concentration (Blanco-Vargas et al 2022 ). Although it is difficult to eliminate all the O 2 in an organic materials mixture, such as the one evaluated, it is possible to reduce it, allowing biochar production to be carried out under reduced oxygen conditions to decrease volatilisation losses and concentrate the solid products (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to eliminate all the O 2 in an organic materials mixture, such as the one evaluated, it is possible to reduce it, allowing biochar production to be carried out under reduced oxygen conditions to decrease volatilisation losses and concentrate the solid products (Table 2 ). Additionally, production costs decrease as it would not be necessary to continuously introduce an inert gas into the muffle to maintain 100% oxygen-free conditions (Moreno-Bayona et al 2019 ; Blanco-Vargas et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations